The global reality of the Paralympic Movement: Challenges and opportunities in disability sports - Eliane Mauerberg-deCastro; Debra Frances Campbell; Carolina Paioli Tavares (Motriz: Revista de Educacao Fisica)
Abstract The purpose of this study was to briefly illustrate some of the challenges and realities of national and international Paralympic sports. The elite disabled athlete paradigm is still not widely known in the world of regular sports competitions. The winning elite disabled athletes are restricted to a few countries, including the U.S., Canada, Germany, China, and Australia, with limited distribution of disability sport opportunities in other countries. This tendency for the success of a minority of countries reflects global problems of social vulnerability in accessibility (e.g., in dismantling the stigma of disability), political vulnerability (e.g., representative organizations of sports for the disabled do not fully pratice the philosophy of "sport for all"), and economic vulnerability (e.g., lack of opportunities for training, assistive sports technology, and sponsorships). Furthermore, elite Paralympic athletes have become veterans. For example, the participation of Brazilian elite athletes in the 1984 Paralympics marked the beginning of a new generation of athletes (approximately 16%) who returned to the Games in 1988. In both 2008 and 2012, nearly 28% of total participants were Brazilian veterans. Although this picture reveals longevity of athletes in the sport, there are many limitations in sports accessibility, often due to geographical centralization of opportunities in large urban centers. Yet, today, the world of Paralympic sport has been transformed into a sports spectacle, thanks to the exceptional performance of some athletes, to the technology of mass communication, and to the support of audiences during the Games. These sport "superstars" offer the world new images and new constructs of "ability." While this forum has helped to bring attention to these "heroes," other Brazilian athletes (and from other countries as well) are still waiting for their opportunities. Indeed, worldwide, young blind individuals, those in wheelchairs, amputees, or simply the uncoordinated, expect to play, run, swim, and take part in the international model of "sport for all." They expect sports opportunities to be a part of their daily lives, an option for rehabilitation and the preservation of health, and a basic human right.